Long-range navigation for resource-constrained planetary rovers using angle of arrival - Takayuki ISHIDA (The Japan Society of Mechanical Engineers, 2015)
This study presents a new navigation system consisting of a resource-constrained rover and landers for planetary long-range exploration. During the exploration, they communicate with each other using radio and the rover receives signals from the landers which contain Angle of Arrival (AOA) data. The rover estimates its position using AOA data. Although obtaining AOA data generally requires a complex device and is difficult to apply to navigation for small rovers. In this study, we implement AOA-based navigation for a resource-constrained rover by rotating a directional antenna such as the high-gain antenna of the landers. In this case, since the rover obtains signals containing AOA data intermittently, we employ an event-driven extended Kalman filter to implement real-time navigation. Our proposed method has the advantage that the rover does not need navigation cameras or sun sensors, and it is therefore suitable for resource-constrained rovers. We developed a small rover and several landers, and conducted experiments in a wide range of Black Rock Desert in America, using the small rover and the landers to obtain the experimental data of AOA which is difficult to simulate. The experimental data are used in numerical simulation. We also validate some cases where there is one lander. These results show the effectiveness of our proposed navigation system using AOA data from the landers in long-range exploration.